Carbon Allocation in Multi-Product Steel Mills That Co‐process Biogenic and Fossil Feedstocks and Adopt Carbon Capture Utilization and Storage Technologies - Biermann, Maximilian; Montañés, Rubén M.; Normann, Fredrik; Johnsson, Filip (Frontiers in Chemical Engineering, 2020)
This work investigates the effects of carbon allocation on the emissions intensities of low-carbon products co-generated in facilities that co-process biogenic and fossil feedstocks and apply carbon capture utilization and storage (CCUS) technology. Thus, these plants simultaneously sequester CO2 and synthesize fuels or chemicals. We consider an integrated steel mill that injects biomass into the blast furnace, captures CO2 for storage and ferments CO to ethanol from the blast furnace gas (BFG). We examine two schemes to allocate the CO2 emissions avoided [due to the renewable feedstock share (biomass) and CO2 capture and storage (CCS)] to the products of steel, ethanol, and electricity (generated through the combustion of steel mill waste gases): 1) allocation by (carbon) mass, which represents actual carbon flows; and 2) a free-choice attribution that maximizes the renewable content allocated to electricity and ethanol. With respect to chosen assumptions on process performance and heat integration, we find that allocation by mass favors steel and is unlikely to yield an ethanol product that fulfils the Renewable Energy Directive (RED) biofuel criterion (65% emission reduction relative to a fossil comparator), even when using renewable electricity and applying CCS to the BFG prior to CO conversion into ethanol and electricity. In contrast, attribution fulfils the criterion and yields bioethanol for electricity grid intensities <180 gCO2/kWhel without CCS, and yields bioethanol for grid intensities up to 800 gCO2/kWhel with CCS. The overall emissions savings are up to 27% and 47% in the near-term and long-term future, respectively. The choice of allocation scheme greatly affects the emissions intensities of co-generated products. Thus, the set of valid allocation schemes determines the extent of flexibility that manufacturers have in producing low-carbon products, which is relevant for industries whose products target sectors that value emissions differently. We recommend that policymakers consider the emerging relevance of co-processing in non-refining facilities. Provided there is no double-accounting of emissions, policies should contain a reasonable degree of freedom in the allocation of emissions savings to low-carbon products, so as to promote the sale of these savings, thereby making investments in mitigation technologies more attractive to stakeholders.